Translation Equivalence in English-Indonesia Text - Dwinta Anggun Ummami (Vivid: Journal of Language and Literature, 2019)
The needs of translation have been increasing in the Industrial Revolution 4.0 as more literature needs to be translated into Bahasa Indonesia. To make use of this opportunity correctly, it is a need to check the equivalence of translation. This present study aims to see translation equivalence of English-Indonesia text translated by the students of English department at State University of Padang. It was designed as descriptive research. The participants were the fourth year students of English department of State University of Padang. The data were collected through a translation test and analyzed by using theories of equivalence. The finding of the research shows that translation equivalence is considered low, as many students create inequivalence translation in the level of lexical, grammatical, and textual, respectively. Since equivalent translation is the goal of every translation, translators who are facing the development of industrial revolution 4.0 need to pay attention to the importance of equivalence in translation.